Fungal encephalitis in human autopsy cases is associated with extensive neuronal damage but only minimal repair. Issue 5 (August 2014) - Tauber, Simone C.; Eiffert, Helmut; Kellner, Silvia; Lugert, Raimond; Bunkowski, Stephanie; Schütze, Sandra; Perske, Christina; Brück, Wolfgang; Nau, Roland
<x xml:space="preserve">Abstract</x> Aims The present study aimed at examining neuronal injury and repair in post mortem brain sections of humans who died from fungal central nervous system infections. Methods Histological and immunohistochemical abnormalities in 15 autopsy cases with fungal central nervous system infections from 1990 to 2008 were compared with findings in 10 age‐ und sex‐matched control cases that died from acute non‐neurological causes. The fungal pathogens were identified by culture or polymerase chain reaction and morphology in post mortem tissue. Seven patients with fungal encephalitis had either an organ transplantation or a malignant haematological disorder; five out of 15 did not have a classical predisposing illness but suffered from severe septic infections as the principal cause of immunosuppression, and three from alcoholism. Results Fungal organisms detected were Aspergillus spp. and other moulds, Candida spp. and black yeast‐like fungi including Cladosporium spp. Histological analyses identified microglial activation, astrocytosis and axonal injury in the white matter without additional demyelination as characteristic features of this infectious disease. An increased rate of hippocampal neuronal apoptosis was detected in fungal encephalitis, while the number of recently generated TUC‐4 and calretinin‐expressing neurones in the dentate gyrus did not differ between patients and controls. Conclusions Unlike in other infectious diseases of the nervous system where a coexistence of damage and repair was observed, fungal encephalitis is characterized by strong damage and minimal neuronal regeneration.